On the dynamics of media markets: Professor Karl Erik Gustafsson in memoriam. Issue 2 (3rd April 2019) - Ots, Mart; Weibull, Lennart; Melesko, Stefan
ABSTRACT: Media and advertising markets have a number of characteristics that affect how firms are competing and collaborating, how new firms enter the markets, and how new products are created. Throughout a research career in media management and media economics that started in the 1960s and stretched over more than five decades, Karl Erik Gustafsson kept exploring these topics, and their implications for both business strategy, regulation, and policy. His work formed early building blocks, both for media management as an academic field, and for the design, operationalisation, and governance of media policy, especially concerning newspaper development, in the Nordic countries. This article provides an introduction to his work.